Peran Mediasi Pertumbuhan Ekonomi pada Pengaruh Desentralisasi Fiskal terhadap Ketimpangan Pendapatan Daerah - Luluk Desva Fitriah; Diah Hari Suryaningrum (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2023)
This study aims to examine and prove the effect of fiscal decentralization on regional income inequality with economic growth as a mediating variable. This study is quantitative. The research population is provincial governments in Indonesia in 2017-2021. Sample selection using purposive sampling techniques. The research sample amounted to 15 provincial governments. Data analysis technique in this study using Structural Equation Modeling Partial Least Square (SEM-PLS) with WarpPLS 7.0 software. The results showed that fiscal decentralization has no effect on regional income inequality. Fiscal decentralization affects economic growth. Economic growth affects regional income inequality. Fiscal decentralization with economic growth as a mediating variable affects regional income inequality. The implication of this research is fiscal decentralization that has been running needs to be optimized. This is to realize equitable distribution of regional income and increase economic growth. In addition, the government needs to pay special attention to areas that have high economic growth rates. However, it is followed by a high income inequality.